Electron Density of Adipose Tissues Determined by Phase-Contrast Computed Tomography Provides a Measure for Mitochondrial Density and Fat Content - Birnbacher, Lorenz; Maurer, Stefanie; Scheidt, Katharina; Herzen, Julia; Pfeiffer, Franz; Fromme, Tobias (Frontiers in Physiology, 2018)
Phase-contrast computed tomography is an X-ray-based imaging method measuring differences in the refractive index during tissue passage. While conventional X-ray techniques rely on the absorption of radiation due to differing tissue-specific attenuation coefficients, phase-contrast computed tomography enables the determination of the electron density. By the analysis of respective phantoms and ex vivo specimens, we identified the components responsible for different electron densities in murine adipose tissue depots to be cellular fat and mitochondrial content, two parameters typically different between white and brown adipose tissue. Brown adipocytes provide mammals with a means of non-shivering thermogenesis to defend normothermia in a cold environment. Brown adipocytes are found in dedicated brown adipose tissue depots and interspersed within white fat depots, a cell type referred to as brite (brown in white) adipocyte. Localization and quantification of brown and brite adipocytes in situ allows an estimate of depot thermogenic capacity and potential contribution to maximal metabolic rate in the cold. We utilized phase-contrast computed tomography to infer the composition of white, brite and brown adipose tissue from electron density of individual depots. As proof of principle, we imaged mice 10, 20 and 30 days of age. During this period, several white adipose tissue depots are known to undergo transient browning. Based on electron density, classical white and brown adipose tissue could be clearly distinguished. Retroperitoneal and inguinal white adipose tissue depots increased transiently in electron density during the known remodeling from white to brite/brown and back to white. We systematically analyzed 18 anatomically defined adipose tissue locations and identified changes in fat content and mitochondrial density that imply an orchestrated pattern of simultaneous browning and whitening on the organismic level. Taken together, phase-contrast computed tomography provides a three-dimensional imaging technique to visualize electron density of tissues in situ. Within the adipose organ, electron density provides a measure of mitochondrial density and fat content. Depending on experimental setting, these constitute surrogate markers of cellular distribution of white, brite and brown adipocytes and thereby an estimate of thermogenic capacity.